Social Policy Review 16 : Analysis and debate in social policy, 2004 - Powell, Martin A. (Book collections on Project MUSE., 2004)
Social Policy Review 16 is an excellent source of information and opinion about core aspects of contemporary social policy for students and academics alike. It will also appeal to all those with an interest in 'welfare' in the widest sense of the term.